On the dynamical mechanisms explaining the western Pacific subsurface temperature buildup leading to ENSO events. Issue 8 (19th April 2015) - Ballester, Joan; Bordoni, Simona; Petrova, Desislava; Rodó, Xavier
Abstract Despite steady progress in the understanding of El Niño–Southern Oscillation (ENSO) in the past decades, questions remain on the exact mechanisms explaining the heat buildup leading to the onset of El Niño (EN) events. Here we use an ensemble of ocean and atmosphere assimilation products to identify mechanisms that are consistently identified by all the data sets and that contribute to the heat buildup in the western Pacific 18 to 24 months before the onset of EN events. Meridional and eastward heat advection due to equatorward subsurface mass convergence and transport along the equatorial undercurrent are found to contribute to the subsurface warming at 170°E–150°W. In the warm pool, instead, surface horizontal convergence and downwelling motion have a leading role in subsurface warming. The picture emerging from our results highlights a sharp dynamical transition at 170°E near the level of the thermocline.